#TITLE_ALTERNATIVE# - Unggul Baroto (NIM 122 03 006) , Whisnu
In a wet gas pipeline transportation system, multiphase flow phenomena would easily occur. This happens because condensate forming along the pipeline deeply affected by multi component within the wet gas. Besides, pressure and temperature gradient take place along the pipeline also affect condensate forming. This study pertains about several parameters that affect pressure gradient and liquid holdup forming along a wet gas pipeline on a particular pipeline system in East Kalimantan region. Those parameters are gas flow rate, pipeline diameter, and pipeline inclination. To investigate the effect of those parameters, compositional multiphase simulator, Pipephase Tacite is used. The system consist of 36 and 42 inch diameter of wet gas pipeline with operating condition and gas composition obtained from field data. Pipeline profile and inclination used in this study is a simplified profile. From the simulation results, in order to minimize liquid holdup forming along the pipeline, gas flow rates must be maintained at 700 and 900 MMSCFD for 36 and 42 inch pipeline diameter, respectively.